If x = -10 and x + √7 – 7p = -3 solve for p

Question

If x = -10 and x + √7 – 7p = -3 solve for p

in progress 0
Sadie 3 days 2021-09-15T17:41:17+00:00 1 Answer 0

Answers ( )

    0
    2021-09-15T17:42:35+00:00

    Answer:

    Hence, in the given expression,  p  =  -0.6220

    Step-by-step explanation:

    Here, the given expression is:

    x = -10 and

    x + √7 – 7 p = -3

    Now, substitute x = -10 in the second equation, we get:

    x + √7 – 7 p = -3  ⇒ -10 + √7 – 7 p = -3

    Substituting √7 = 2.645751

    Solving, it further, we get

    -10 + √7 – 7 p = -3

    -10 + 2.645751  + 3  = 7 p

    or,   -4.354248  =  7 p

    or,  p =  -4.354248/7 =  -0.6220

    or, p  =  -0.6220

    Hence, in the given expression, p  =  -0.6220

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )